KHAMR IN THE QUR'AN (THEMATIC STUDY OF TAFSIR IBN JARIR AL-TABARI) - Ridho Adiansyah; Nurul Faezah binti Yahya (Universitas Muhammadiyah Surakarta, 2023)
Food and drink are basic needs for humans to meet the body's intake needs, both for growth and for energy in daily activities. Allah SWT. ordered people to look for food and drink that is lawful and good (Qs. al-Baqarah / 2: 168, 172) This has been regulated since the revelation of the Islamic treatise. In Islamic law, it is strictly prohibited and even forbidden to consume drinks containing alcohol, such as khamr and the like. However, there are still many cultural phenomena in certain Muslim societies where people consume alcoholic beverages, or khamr, and do not pay attention to the effects of consuming alcohol. This research focuses on issues related to the need for a new interpretation that is more contextual by using the object of the al-Tabari interpretation book as the main reference. Because the book of al-Tabari, contains a wealth of sources and previous history, especially in terms of the meaning of words and the use of Arabic. In this essay, the author uses a type of library research (library research) using a descriptive-analytical method. The results of the research show that Allah SWT. really loves and cares for each of his servants so they don't fall into immoral behavior, such as khamr and the like. Because khamr is very dangerous for the health of the human body, and can cause a loss of awareness of reason and intellectual abilities.